Knowledge co-production in practice: Enabling environmental management systems for ports through participatory research in the Dutch Wadden Sea. Issue 55 (January 2016) - Puente-Rodríguez, Daniel; van Slobbe, Erik; Al, Iris A.C.; Lindenbergh, D.E. (Danny)
Highlights: We explore knowledge co-production practices in the Dutch Wadden Sea. Participation is deployed to develop port's environmental management systems (EMS). We analyze the process of emergence, standardization, and enculturation of EMS. Knowledge arrangements and co-production required to stabilize EMS in port-practices. Abstract: Coastal zone management is inconceivable without the mobilization and integration of different types of knowledge – that is, without knowledge co-production practices. This article applies the concept of knowledge co-production to analyze the process of emergence, standardization, and enculturation of environmental management systems (EMSs) within port communities in the Dutch Wadden Sea. Moreover, it is a report from the field in which we reflect on the participatory practices conducted to facilitate the knowledge arrangements required to develop EMSs for a group of ports. The article concludes that this type of knowledge arrangement and co-production practices (involving different types of actors and knowledge) might become mandatory in the near future to stabilize the EMS phenomenon in the practices of ports.